SARS-CoV-2 surveillance system in Canada: Longitudinal trend analysis - Post, Lori; Boctor, Michael J.; Issa, Tariq Z.; Moss, Charles B.; Murphy, Robert L.; Resnick, Danielle (JMIR Publications, 2021)
The COVID-19 global pandemic has disrupted structures and communities across the globe. Numerous regions of the world have had varying responses in their attempts to contain the spread of the virus. Varying factors such as public health policies, governance, and sociopolitical factors, have led to differential levels of success at controlling the spread of SARS-CoV-2. Ultimately, a more advanced surveillance metric for COVID-19 transmission is necessary to help government systems and national leaders understand which responses have been effective and gauge where outbreaks occur.